Homeowner flood risk and risk reduction from home elevation between the limits of the 100- and 500-year floodplains - Al Assi, Ayat; Mostafiz, Rubayet Bin; Friedland, Carol J.; Rohli, Robert V.; Rahim, Md Adilur (Frontiers in Earth Science, 2023)
Floods inflict significant damage even outside the 100-year floodplain. Thus, restricting flood risk analysis to the 100-year floodplain (Special Flood Hazard Area (SFHA) in the U.S.A.) is misleading. Flood risk outside the SFHA is often underestimated because of minimal flood-related insurance requirements and regulations and sparse flood depth data. This study proposes a systematic approach to predict flood risk for a single-family home using average annual loss (AAL) in the shaded X Zone – the area immediately outside the SFHA (i.e., the 500-year floodplain), which lies between the limits of the 1.0- and 0.2-percent annual flood probability. To further inform flood mitigation strategy, annual flood risk reduction with additional elevation above an initial first-floor height (FFH0) is estimated. The proposed approach generates synthetic flood parameters, quantifies AAL for a hypothetical slab-on–grade, single-family home with varying attributes and scenarios above the slab-on-grade elevation, and compares flood risk for two areas using the synthetic flood parameters vs. an existing spatial interpolation-estimated flood parameters. Results reveal a median AAL in the shaded X Zone of 0.13 and 0.17 percent of replacement cost value (V_R) for a one-story, single-family home without and with basement, respectively, at FFH0 and 500-year flood depth < 1 foot. Elevating homes one and four feet above FFH0 substantially mitigates this risk, generating savings of 0.07–0.18 and 0.09–0.23 percent of V_R for a one-story, single-family home without and with basement, respectively. These results enhance understanding of flood risk and the benefits of elevating homes above FFH0 in the shaded X Zone.